2014
DOI: 10.1038/ijo.2014.201
|View full text |Cite
|
Sign up to set email alerts
|

Social jetlag, obesity and metabolic disorder: investigation in a cohort study

Abstract: BACKGROUND Obesity is one of the leading causes of preventable death worldwide. Circadian rhythms are known to control both sleep timing and energy homeostasis, and disruptions in circadian rhythms have been linked with metabolic dysfunction and obesity-associated disease. In previous research, social jetlag, a measure of chronic circadian disruption caused by the discrepancy between our internal versus social clocks, was associated with elevated self-reported body mass index, possibly indicative of a more gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
287
3
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 358 publications
(312 citation statements)
references
References 41 publications
15
287
3
7
Order By: Relevance
“…data on height and weight in one study 21 versus assessment of BMI variables by staff members in another, 22 or to different sample characteristics, since Roenneberg et al 21 studied individuals primarily from central Europe with a broader age range, while Johnsen et al 22 investigated a population located at higher latitudes, above the Arctic Circle. Corroborating the hypothesis of the influence of latitude, Parsons et al 23 found an association between SJL and higher BMI, fat mass and probability of being obese (BMI ≥30 kg/m 2 ) in individuals from midlatitudes, while Polugrudov et al 24 found no association of SJL with BMI and waist circumference in a population living in the subarctic. Furthermore, none of these studies controlled the results for energy intake, energy expenditure or body fat.…”
Section: Excluded Studies and Terminologymentioning
confidence: 99%
See 1 more Smart Citation
“…data on height and weight in one study 21 versus assessment of BMI variables by staff members in another, 22 or to different sample characteristics, since Roenneberg et al 21 studied individuals primarily from central Europe with a broader age range, while Johnsen et al 22 investigated a population located at higher latitudes, above the Arctic Circle. Corroborating the hypothesis of the influence of latitude, Parsons et al 23 found an association between SJL and higher BMI, fat mass and probability of being obese (BMI ≥30 kg/m 2 ) in individuals from midlatitudes, while Polugrudov et al 24 found no association of SJL with BMI and waist circumference in a population living in the subarctic. Furthermore, none of these studies controlled the results for energy intake, energy expenditure or body fat.…”
Section: Excluded Studies and Terminologymentioning
confidence: 99%
“…Kantermann et al 25 found no association between SJL and metabolic risk parameters in male shift workers, which may be due to the small sample size. However, Parsons et al 23 found that individuals with higher SJL were more likely to meet the criteria for metabolic syndrome and Wong et al 26 found higher cardiometabolic risk markers associated with higher SJL in larger samples of both sexes. Regarding the risk of cardiovascular pathologies, a positive correlation between SJL and heart rate has been demonstrated.…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…A less extreme form of living against our internal body clock, but which affects far more people, is caused by the so-called social jetlag (30) . Social jetlag is the discrepancy between our internal body clocks and our social clock and this has also been associated with increased risk for non-communicable chronic diseases such as obesity (30) and the metabolic syndrome (7) . It has been estimated that social jetlag affects more than 80 % of the general population in central Europe (30) , especially people living in urban areas.…”
Section: Shift Workers Disease Risk and Dietary Patternsmentioning
confidence: 99%
“…It has been hypothesised that consuming irregular or inconsistent meals affects our internal body clock, also called chrono-biological or circadian rhythms, and could thereby have an impact on metabolic disease risk. Circadian rhythms are biological rhythms that follow a 24 h cycle, from Latin meaning 'approximate day' (7) . It is known that many physiologically and nutritionally relevant processes in the human body have circadian rhythms, including glycolysis and gluconeogenesis, cholesterol and lipid metabolism, oxidative phosphorylation and detoxification pathways (8,9) .…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%
“…Additionally, social jet lag was also associated with indicators of inflammation and diabetes in "metabolically unhealthy" obese participants. 91 Delaying bedtime by 8.5 hours for 4 days decreases insulin sensitivity and inflammation. 92 Endocrine rhythms, specifically leptin and melatonin, are depressed in night active individuals, defined as having an average sleep onset of 01:30 hours relative to 22:30 hours in control participants.…”
mentioning
confidence: 99%